On the importance of fiscal space: Evidence from short sellers during the COVID-19 pandemic - Stefan Greppmair; Stephan Jank; Esad Smajlbegovic (Deutsche Bundesbank, 2021)
Using the exogenous shock of the COVID-19 pandemic, we study how informed market participants evaluate fiscal space. Short-selling activity shifted upon the onset of the pandemic towards companies with low financial flexibility only in countries with limited fiscal space. Among these companies, short sellers targeted especially those that generate their revenue mainly in the domestic market. These short sellers entered their positions before the market crash, generating thereby a significant abnormal return. These findings support the notion that short sellers bet on the inability of governments with budgetary constraints to provide sufficient stimulus to their economy in times of crises.
Keywords: G14; G23; H30; 330; COVID-19 pandemic; short selling; fiscal space; institutional investors